Development of Communicative-Based Teaching Materials in Aqidah Akhlaq Subjects - Novia Maharani Permatasari; Amrini Shofiyani (SCHOOLAR: Social and Literature Study in Education, 2022)
This research entitled "Development of Communicative-Based Teaching Materials in Aqidah Akhlaq Subjects "aims to improve learning by choosing the right strategy, procurement of efficient and interesting teaching materials. Also in order to achieve the learning target in accordance with the provisions set. Therefore, teaching materials are the most important component in learning. One of the main elements or urgent parts of the curriculum is teaching materials. Therefore the teacher as someone who delivers students to achieve goals or competencies, and must understand the principles in the development of teaching materials. In the new normal some schools use an online system, it is necessary to have communicative teaching materials so that they can be used and learned independently by students. Especially in a class that in fact has just entered junior high school. So it can help students in understanding online learning materials are felt less. Moreover, learning aqidah akhlaq to shape the personality of students in order to have a strong faith and laughter. so that his life is decorated with noble akhlaq.